Does Fiscal Decentralisation Foster Regional Convergence? - Blöchliger, Hansjörg (OECD Publishing, 2016)
Across the OECD, GDP per capita is converging. In contrast, regional disparities - or differences in GDP per capita across jurisdictions - are rising, mainly as a result of widening productivity differences. Fiscal decentralisation could help reduce them again. According to new OECD research, assigning more ownsource revenue to sub-national governments dampens regional GDP disparities and underpins regional convergence. In more decentralised settings, catching-up regions appear to adopt policy innovations more rapidly and their policy innovations have a stronger impact. Conversely, intergovernmental grants tend to fuel disparities, probably because they discourage lagging regions to develop their economic and fiscal base. However, when replacing intergovernmental transfers by own-source revenue, lower disparities in regional output may come at the cost of larger disparities in regional income and more unequal public service standards. Reforms to intergovernmental fiscal frameworks should therefore be two-pronged: a rise in sub-national own-source revenue should be paired with a re-design of intergovernmental transfers and fiscal equalisation, in order to make all jurisdictions enjoy the benefits of more sub-central fiscal power
Keywords: Economics